2018
DOI: 10.21037/jtd.2018.04.132
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of triglycerides with myocardial infarction and analysis of risk factors for myocardial infarction in patients with elevated triglyceride

Abstract: In the study population of the Kailuan region, elevated fasting TG increases the risk of MI, particularly in populations with an age of ≥65 years old, BMI >25 kg/m, FBG ≥6.1 mmol/L and HDL-C <1.5 mmol/L.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 22 publications
2
8
0
Order By: Relevance
“…Combining the two complementary stories of metabolite and lipid dysregulation before and after exercise and a PMI provides an important assessment of their biological changes (Figures 3 and 4). This comparison is incredibly insightful for understanding CVD pathophysiology, as shown by comparing our results with the general consensus of molecular dysregulation from several exercise, CVD onset and MI studies (Figure 6) [4,24,51,52,61,69,78]. Results from the CVD onset studies have illustrated upregulation of sphingolipids and carnitines, and shown downregulation of lyso PC and DGs.…”
Section: Study Comparisonsupporting
confidence: 67%
See 2 more Smart Citations
“…Combining the two complementary stories of metabolite and lipid dysregulation before and after exercise and a PMI provides an important assessment of their biological changes (Figures 3 and 4). This comparison is incredibly insightful for understanding CVD pathophysiology, as shown by comparing our results with the general consensus of molecular dysregulation from several exercise, CVD onset and MI studies (Figure 6) [4,24,51,52,61,69,78]. Results from the CVD onset studies have illustrated upregulation of sphingolipids and carnitines, and shown downregulation of lyso PC and DGs.…”
Section: Study Comparisonsupporting
confidence: 67%
“…Conversely, PC lipids which have overlapping roles as charged species enriched within the outer lipid membrane layer were downregulated following a PMI [ 59 ]. Additionally, a general downregulation of glycerolipids was also detected following a PMI event, a contradictory finding to the positive correlation of TGs and MI incidence [ 60 , 61 ] This finding may instead reflect FAs serving as the primary energy substrates of the heart where non-esterified FAs, products of glycerolipids degradation, are rapidly complexed with CoA [ 62 ]. Notably, ceramides which have previously been positively correlated with cardiac disease risk were not observed to be statistically significant in our PMI cohort [ 63 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, we did not find any relationship between HDL-C levels in subjects carrying the G allele compared to noncarriers, which is consistent with findings reported by other studies [ 29 , 33 , 36 ]. A recent study showed that elevated levels of fasting TG are significantly associated with increased risk of myocardial infarction and gradually decreased levels of HDL-C [ 45 ]. Despite this negative correlation that have been shown between HDL-C and plasma TG in several studies, there was no evidence of any association between decreased HDL-C levels and the APOA5 G allele [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…The global incidence of MI was 2483 per 100,000 in 2016 [2], and MI accounts for about one million deaths in China annually [3]. Previous investigations revealed that dyslipidemias has a major and causal role in MI development, and that MI incidence increases with high total cholesterol (TC) levels, high low-density https://doi.org/10.1016/j.atherosclerosis.2020.03.026 Received 6 November 2019; Received in revised form 22 February 2020; Accepted 27 March 2020 lipoprotein cholesterol (LDL-C) levels, high triglyceride (TG) levels, high non-high-density lipoprotein cholesterol (non-HDL-C) levels, and low high-density lipoprotein cholesterol (HDL-C) levels [4][5][6][7][8][9]. However, recent studies [10,11] have indicated that lipid level evaluation at a single time point may yield a biased estimate of the relationships between lipid levels and MI risk, and that changes in lipids may be an important factor for accurate prediction of MI risk.…”
Section: Introductionmentioning
confidence: 99%